Aluminum-copper alloy micro-arc oxidation film layer and preparation method thereof

By optimizing the electrical parameters and electrolyte composition, the problems of unevenness and low corrosion resistance in the preparation of microarc oxide film are solved, and the densification and corrosion resistance of aluminum-copper alloy microarc oxide film layer are achieved.

CN119221069APending Publication Date: 2024-12-31CHIFENG UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411349872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the existing microarc oxidation preparation process, there are problems such as complex electrical parameter control, uneven film layer, insufficient adhesion and bonding strength, low preparation efficiency and low corrosion resistance.

Method used

By optimizing the electrical parameter setting and screening of electrolytes in the electrolyte, a microarc oxidized electrolyte composed of sodium silicate, sodium hydroxide and soluble oxalate is used to optimize the current density, pulse frequency and duty cycle to improve the film formation efficiency , reduce the porosity of the microarc oxide film layer of aluminum-copper alloy, and enhance the corrosion resistance of the film layer.

Benefits of technology

The densification of the aluminum-copper alloy microarc oxide film layer is achieved, the bonding force and corrosion resistance of the film layer are improved, the preparation efficiency and the protection performance of the film layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221069A_ABST
    Figure CN119221069A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum-copper alloy surface treatment, in particular to an aluminum-copper alloy micro-arc oxidation film layer and a preparation method thereof.The preparation method comprises the following steps that a base material is pretreated; a micro-arc oxidation electrolyte is prepared, an electrolyte in the micro-arc oxidation electrolyte is composed of sodium silicate, sodium hydroxide and soluble oxalate, a solvent is water, the pretreated base material is placed in the micro-arc oxidation electrolyte to be subjected to micro-arc oxidation, the aluminum-copper alloy micro-arc oxidation film layer is obtained, and specific electrical parameters of micro-arc oxidation are as follows: the current density is 3A / dm < 2 >-5A / dm < 2 >, the current density is 3A / dm < 2 >-5A / dm < 2 >, and the current density is 3A / dm < 2 >-5A / dm < 2 >-5A / dm < 2 >; according to the method, the porosity of the aluminum-copper alloy micro-arc oxidation film layer is synergistically reduced by optimizing the electrical parameters and the concentration of the electrolyte, and then the corrosion resistance of the film layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-copper alloy surface treatment, and in particular to an aluminum-copper alloy micro-arc oxidation film layer and a preparation method thereof. Background Art

[0002] The micro-arc oxidation (MAO) surface treatment method is popular because it can form an oxide ceramic film with good bonding with the substrate, insulation, corrosion resistance and other characteristics in situ on the surface of aluminum and its alloys through the combined effects of plasma chemical reaction, electrochemical reaction, chemical reaction, thermal diffusion, etc. However, the micro-arc oxidation film has a loose porous structure, and the corrosive medium will reach and destroy the substrate through the defects in the film. How to reduce film defects has always been the key to improving the protective performance of aluminum and its alloys. However, the existing micro-arc oxidation preparation process has the problems of complex electrical parameter control, uneven film layer, insufficient adhesion and bonding strength, low preparation efficiency, and low corrosion resistance of the film layer. Summary of the invention

[0003] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide an aluminum-copper alloy micro-arc oxidation film layer and a preparation method thereof. The present invention first optimizes the electrical parameter setting, and on this basis, screens the electrolyte in the electrolyte, and finally obtains a film preparation scheme, so that the electrical parameter control and the electrolyte work synergistically to improve the film forming efficiency, increase the film layer bonding strength, reduce the porosity of the aluminum-copper alloy micro-arc oxidation film layer, and thereby improve the corrosion resistance of the film layer.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] A method for preparing an aluminum-copper alloy micro-arc oxidation film layer comprises the following steps:

[0006] Pre-treat the base material.

[0007] A micro-arc oxidation electrolyte is prepared, wherein the electrolyte in the micro-arc oxidation electrolyte consists of sodium silicate, sodium hydroxide and soluble oxalate, and the solvent is deionized water.

[0008] The pretreated substrate material is placed in a micro-arc oxidation electrolyte for micro-arc oxidation to obtain an aluminum-copper alloy micro-arc oxidation film layer, wherein the specific electrical parameters of the micro-arc oxidation are: current density 3A / dm 2 ~5A / dm 2 , the pulse frequency is 300Hz~600Hz, and the duty cycle is 12%~18%.

[0009] The present invention first optimizes the electrical parameters of micro-arc oxidation, and on this basis screens the electrolyte in the electrolyte, and prepares an electrolyte system consisting of sodium silicate, sodium hydroxide and soluble oxalate, so that the electrical parameters of micro-arc oxidation and the electrolyte work synergistically to improve the film forming efficiency, increase the bonding strength of the film layer, reduce the porosity of the aluminum-copper alloy micro-arc oxidation film layer, and thus improve the corrosion resistance of the film layer.

[0010] In a preferred embodiment of the present invention, the specific electrical parameters of micro-arc oxidation are: current density is 3A / dm 2 , the pulse frequency is 600Hz and the duty cycle is 12%.

[0011] In a preferred embodiment of the present invention, the soluble oxalate is sodium oxalate, potassium oxalate or ammonium oxalate.

[0012] In a preferred embodiment of the present invention, in the micro-arc oxidation electrolyte, the concentration of sodium silicate is 2.5 g / L to 7.5 g / L, the concentration of sodium hydroxide is 2 g / L to 5 g / L, and the concentration of soluble oxalate is 0.5 g / L to 1.5 g / L.

[0013] In a preferred embodiment of the present invention, the concentration of soluble oxalate is 0.5 g / L.

[0014] In a preferred embodiment of the present invention, the micro-arc oxidation treatment time is 2 hours to 3 hours, and the treatment temperature is 30° C. to 40° C.

[0015] In a preferred embodiment of the present invention, the matrix material is an aluminum-copper alloy.

[0016] Another object of the present invention is to provide an aluminum-copper alloy micro-arc oxidation film layer prepared by any of the preparation methods described above.

[0017] In a preferred embodiment of the present invention, the micro-arc oxidation film has a thickness of 50 μm to 60 μm and a hardness of 1180.42 HV to 1301.94 HV.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention provides an aluminum-copper alloy micro-arc oxidation film layer and a preparation method thereof, wherein a micro-arc oxidation electrolyte composed of sodium silicate, sodium hydroxide and soluble oxalate is prepared, and a pretreated substrate material is placed in the micro-arc oxidation electrolyte for micro-arc oxidation treatment to obtain an aluminum-copper alloy micro-arc oxidation film layer, wherein the specific electrical parameters of the micro-arc oxidation are set as follows: a current density of 3A / dm 2 ~5A / dm 2The pulse frequency is 300Hz-600Hz, and the duty cycle is 12%-18%. The present invention first optimizes the electrical parameters of micro-arc oxidation, and on this basis screens the electrolyte in the electrolyte, so that the micro-arc oxidation electrical parameters and the electrolyte work together to improve the film forming efficiency, increase the bonding strength of the film layer, and reduce the porosity of the aluminum-copper alloy micro-arc oxidation film layer, thereby improving the corrosion resistance of the film layer.

[0020] 2. The present invention adds sodium oxalate to the electrolyte, which has the following main functions: ① Inducing plasma spark discharge; ② Promoting the "conversion" process and increasing the film growth rate; ③ C2O4 2- It has complexing effect and improves the utilization rate of metal ions; ④C2O4 2- The gas contact angle is reduced and gas escape is promoted. Several aspects work synergistically. Compared with the film layer without added sodium oxalate, as the concentration of added sodium oxalate increases, the content of Si and Cu elements in the film layer increases, the thickness of the film layer increases, the defects are significantly reduced, the high-temperature stable phase α-Al2O3 in the film layer increases, the hardness is improved, and the film layer is densified. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Variation curves of (a) duty cycle, (b) current density, (c) pulse frequency and (d) electrolyte concentration on film thickness.

[0022] Figure 2 The variation curves of (a) duty cycle, (b) current density, (c) pulse frequency and (d) electrolyte concentration on film hardness.

[0023] Figure 3 XRD patterns of micro-arc oxidation films prepared with different sodium oxalate concentrations.

[0024] Figure 4 The cross-sectional morphologies of micro-arc oxidation films under different Na2C2O4 concentrations; (a) 0.0g / L; (b) 0.5g / L; (c) 1.0g / L; (d) 1.5g / L; (e) 2.0g / L.

[0025] Figure 5 Element distribution diagram of the cross section of the micro-arc oxidation film under different sodium oxalate concentrations; (a) 0.0g / L; (b) 0.5g / L; (c) 1.0g / L; (d) 1.5g / L; (e) 2.0g / L.

[0026] Figure 6 The potentiodynamic polarization curves of MAO films prepared at different sodium oxalate concentrations.

[0027] Figure 7Bode diagrams of electrochemical impedance spectroscopy of four MAO film layers in 3.5 wt.% NaCl solution: (a) 1 day, (b) 7 days, and (c) 14 days.

[0028] Figure 8 Equivalent circuit diagrams of PEO membrane layers prepared in four solutions immersed in 3.5wt.% NaCl solution for 14 days: (a) R(Q(R(Q(R(Q(RW)))))), (b) R(QR)(Q(R(Q(RW)))), (c) R(Q(R(Q(RW)))).

[0029] Fig. 9 Macroscopic morphology of MAO films prepared with four different concentrations of sodium oxalate after exposure to neutral salt spray test for 0 days, 3 days, 7 days, 11 days, 14 days, 28 days and 45 days.

[0030] Fig.10 This is the plasma spark discharge state of the entire micro-arc oxidation process of 2A12 aluminum-copper alloy in electrolytes with different Na2C2O4 concentrations.

[0031] Fig.11 is the thickness of the MAO film layer prepared at different sodium oxalate concentrations.

[0032] Fig.12 is the hardness of the MAO film prepared at different sodium oxalate concentrations.

[0033] Fig.13 The distribution diagram of Cu and Si elements in the cross section of micro-arc oxidation film under different sodium oxalate concentrations.

[0034] Fig.14 Figure 3. The effect of different concentrations of Na2C2O4 on the growth behavior of micro-arc oxidation films after applying bidirectional pulses: (a) and (b) represent lower concentrations; (c) and (d) represent higher concentrations. DETAILED DESCRIPTION

[0035] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0037] Example 1

[0038] A method for preparing an aluminum-copper alloy micro-arc oxidation film layer comprises the following steps:

[0039] (1) The aluminum-copper alloy was surface pretreated. The specific operation was as follows: all samples were polished using a grinding machine, and the abrasive was SiC water-abrasive sandpaper. The order of use was 120#, 600#, 800#, and finally 2000#; the polished samples were first cleaned with ethanol, then rinsed with deionized water, and then dried with a hair dryer with cold air, and finally placed in a drying dish for use.

[0040] (2) Preparation of micro-arc oxidation electrolyte: First, weigh 600 g of sodium silicate, 250 g of sodium hydroxide and 50 g of sodium oxalate; then, dissolve these chemical reagents in deionized water to prepare a micro-arc oxidation electrolyte with a sodium silicate concentration of 6.0 g / L, a sodium hydroxide concentration of 2.5 g / L, and a sodium oxalate concentration of 0.5 g / L, and a total volume of 100 L.

[0041] (3) The pretreated aluminum-copper alloy was placed in a micro-arc oxidation electrolyte for micro-arc oxidation. The micro-arc oxidation treatment temperature was 30° C. and the treatment time was 2.5 h to obtain an aluminum-copper alloy micro-arc oxidation film layer. The specific parameters of the micro-arc oxidation were: the current density was 3 A / dm 2 , the pulse frequency is 600Hz and the duty cycle is 12%.

[0042] Example 2

[0043] The preparation method is the same as that of Example 1, except that the concentration of sodium oxalate in the micro-arc oxidation electrolyte is replaced with 1 g / L.

[0044] Example 3

[0045] The preparation method is the same as that of Example 1, except that the concentration of sodium oxalate in the micro-arc oxidation electrolyte is replaced with 1.5 g / L.

[0046] Example 4

[0047] The preparation method is the same as that of Example 1, except that the current density is replaced by 5A / dm 2 .

[0048] Example 5

[0049] The preparation method is the same as that of Example 1, except that the pulse frequency is replaced with 300 Hz.

[0050] Example 6

[0051] The preparation method is the same as that of Example 1, except that the duty cycle is replaced with 18%.

[0052] Comparative Example 1

[0053] The preparation method is the same as that of Example 1, except that the concentration of sodium oxalate is replaced with 0 g / L.

[0054] Comparative Example 2

[0055] The preparation method is the same as that of Example 1, except that the concentration of sodium oxalate is replaced with 2 g / L.

[0056] Comparative Example 3

[0057] The preparation method is the same as that of Example 1, except that the current density is replaced by 1 A / dm 2 .

[0058] Comparative Example 4

[0059] The preparation method is the same as that of Example 1, except that the pulse frequency is replaced with 100 Hz.

[0060] Comparative Example 5

[0061] The preparation method is the same as that of Example 1, except that the duty cycle is replaced with 6%.

[0062] Experimental analysis process and result representation

[0063] 1. Optimization of process parameters and determination of basic electrolyte formula

[0064] There are four factors mainly discussed, namely, electrolyte concentration, current density, pulse frequency and duty cycle. Each factor takes three level values, as shown in Table 1. In the electrolyte, the concentration of sodium silicate is 2.5-7.5 g / L, the concentration of sodium hydroxide is 2-5 g / L, and the concentration of sodium oxalate is 0.5-1.5 g / L.

[0065] Table 1 Factors and levels of orthogonal design

[0066]

[0067] The experimental results of hardness test and thickness test are used as the comparative data of orthogonal test, and the thickness and hardness of micro-arc oxidation film are used as the objective function to determine the optimal process conditions. A total of 9 groups of experiments are required, namely A1B1C1D1, A1B2C2D2, A1B3C3D3, A2B1C2D3, A2B2C3D1, A2B3C1D2, A3B1C3D2, A3B2C1D3, A3B3C2D1, as shown in Table 2.

[0068] Table 2 Orthogonal experiment arrangement plan

[0069]

[0070]

[0071] Effect of process parameters on thickness of micro-arc oxidation film

[0072] The data of the prepared sample film thickness are analyzed using Table 3. Objective function 1 is the thickness table of the micro-arc oxidation film. SUM1(J1) is the sum of the thickness at the first level of the four factors, SUM2(J1) is the sum of the thickness at the second level of the four factors, and SUM3(J1) is the sum of the thickness at the third level of the four factors. AVE(J1) is the average of the sums. R1 is the range. The size of AVE(J1) reflects the size of the objective function J at this level, that is, AVE1(J1) reflects the size of the micro-arc oxidation layer thickness at the first level of a certain factor, AVE2(J1) is the size of the micro-arc oxidation layer thickness at the second level of a certain factor, and so on. The range R1 reflects the influence of the factor on the thickness of the micro-arc oxidation film.

[0073] Table 3 Intuitive analysis diagram of objective function 1 (micro-arc oxidation thickness results)

[0074]

[0075]

[0076] It can be seen from Table 3 that the duty cycle of factor D has the largest range, that is, the duty cycle parameter has the greatest influence on the thickness of the micro-arc oxidation film. The current density is the second influencing factor on the thickness of the micro-arc oxidation film. The electrolyte concentration and pulse frequency have relatively little influence on the micro-arc oxidation film.

[0077] from Figure 1 It can be clearly seen that the influence trend of various factors on the thickness of the micro-arc oxidation film. In Figure (a), with the increase of duty cycle, the thickness of the micro-arc oxidation film first increases and then decreases. The duration and density of plasma spark discharge in the micro-arc oxidation process depend on the length and energy of a single pulse, respectively.

[0078] Under different duty cycles, the difference in pulse energy will first affect the thickness of the micro-arc oxidation film. When the duty cycle increases from 6% to 12%, the thickness of the micro-arc oxidation film increases. When the duty cycle is too high, the amplification of the single pulse time and the excessive current cause part of the oxide in the oxidation layer to be sputtered into the electrolyte, so that the thickness does not increase but decreases. (b) In the figure, as the current density increases, the thickness of the micro-arc oxidation film increases, and it is close to a linear increase within the factor level range of the experimental design. When the current density increases, the energy allocated to each plasma micro-zone increases, which helps to increase the instantaneous temperature of the plasma micro-zone, so that more ions participate in the reaction, and thus the growth rate of the micro-arc oxidation film is accelerated. (c) In the figure, as the pulse frequency increases, the thickness of the micro-arc oxidation film does not change much, indicating that the pulse frequency has little effect on the growth rate of the micro-arc oxidation layer, but the pulse frequency will affect the surface morphology of the micro-arc oxidation layer. When the frequency is relatively low, the surface is rough and the pores are larger. When the pulse frequency is increased, the micropores on the surface of the micro-arc oxidation film gradually decrease in diameter, the number increases, and the surface flatness increases. (d) In the figure, within the range of experimental factor levels, the electrolyte concentration increases. When the electrolyte concentration increases from 5g / L to 9g / L, the thickness of the micro-arc oxidation film increases by about 50%. However, after the concentration increases to a certain level, the film thickness will no longer increase, but will decrease slightly.

[0079] Effect of process parameters on microhardness of micro-arc oxidation films

[0080] Objective function 2 is the microhardness of the micro-arc oxidation film. SUM1(J2) is the sum of all hardness values ​​of the first level of the four factors, SUM2(J2) is the sum of all hardness values ​​of the second level of the four factors, and SUM3(J2) is the sum of all hardness values ​​of the third level of the four factors. AVE(J1) is the average value of the sum, and so on. R2 is the range.

[0081] Table 4 Objective function 2 (micro-arc oxidation layer hardness)

[0082]

[0083] It can be seen from Table 4 that the extreme values ​​of the duty cycle of factor D and the current density of factor A are close, indicating that the two factors have a greater influence on the hardness of the micro-arc oxidation film, while the electrolyte concentration of factor B and the pulse frequency of factor C have less influence on the hardness of the micro-arc oxidation layer.

[0084] Depend on Figure 2It can be seen from Figure (a) that as the duty cycle increases, the microhardness of the micro-arc oxidation film increases. As the duty cycle increases, the discharge time and energy of a single pulse increase, resulting in more γ-Al2O3 being transformed into α-Al2O3. The increase in the α-Al2O3 component increases the microhardness of the micro-arc oxidation layer. Figure (b) shows that as the current density increases, the microhardness of the micro-arc oxidation film increases. Within a certain range of oxide layer thickness, the size of the micro-arc oxidation layer hardness is approximately proportional to the thickness of the micro-arc oxidation layer, but too high a current density will cause the micro-arc oxidation film to burn and damage. Figure (c) shows that as the pulse frequency increases, the microhardness of the micro-arc oxidation layer shows an upward trend. If the frequency is too high, surface local discharge ablation will occur, and the frequency setting should not be too high. Figure (d) shows that as the electrolyte concentration increases, the microhardness of the micro-arc oxidation layer gradually increases, but the increase is relatively gentle. The effect of electrolyte concentration on micro-arc oxidation conforms to the "impurity center discharge model". When the electrolyte concentration is low, the number of electrolyte particles entering the oxide layer is small, that is, electron avalanche occurs, and the dynamic fluctuation effect caused becomes dominant. When the electrolyte concentration is high, more electrolyte particles enter the oxide layer, and more impurity release centers are formed. When many electrons undergo electron avalanche at the same time, the dynamic fluctuation effect caused will be significantly manifested. When the electrolyte concentration is higher than a certain value, the dynamic fluctuation effect caused by continuous avalanche plays a dominant role. At this time, the properties of the micro-arc oxidation film layer on the surface of the treated aluminum substrate will also fluctuate due to the dynamic fluctuation effect caused by continuous avalanche. Therefore, through Figure 1 (d) and Figure 2 (d) The analysis shows that the thickness of the micro-arc oxidation film does not increase monotonically, but fluctuates, and the growth rate of the microhardness is slow.

[0085] Therefore, the optimized process parameters are sodium silicate concentration of 6.0 g / L, sodium hydroxide concentration of 2.5 g / L, sodium oxalate concentration of 0.5 g / L, and current density of 3 A / dm 2 , pulse frequency 600Hz, duty cycle 12%.

[0086] 2. Composition, microstructure and performance characterization of micro-arc oxidation films prepared in electrolytes with different NaC2O4 concentrations

[0087] (1) XRD spectrum analysis

[0088] The X-ray diffraction analysis results of the micro-arc oxidation film of 2A12 aluminum alloy prepared in electrolyte with different concentrations of sodium oxalate are shown in Figure 2. Figure 3As shown. The four MAO film layers are mainly composed of α-Al2O3 and γ-Al2O3. In addition, the diffraction peak of Al appears because X-rays can detect matrix information through the pores of the film layer. With the continuous increase of sodium oxalate concentration, α-Al2O3 continues to increase. During the micro-arc oxidation reaction, due to the violent arc discharge phenomenon, the temperature of the oxidation micro-area rises sharply, the Al in the matrix melts and undergoes ionization reaction. At the same time, the film layer will also melt or even vaporize, and Al 3+ Reacts with OH- in the electrolyte to form Al(OH)3. Al(OH)3 then continues to react to form Al2O3. As the temperature contained in the film increases, the Al2O3 in the film is transformed into a high-temperature metastable phase γ-Al2O3. When the micro-area oxidation temperature of the film exceeds 1200°C, the high-temperature metastable phase γ-Al2O3 is transformed into a stable phase α-Al2O3. Compared with the film obtained by adding Na2C2O4, the diffraction peak intensity of the 0g / L sodium oxalate film at 25.58, 35.15, 43.36, and 57.50 is significantly weaker than that of other film layers. From the above differences, it can be inferred that the film layer after micro-arc oxidation without the addition of sodium oxalate is relatively loose and porous, and the solution quickly enters the film layer, thereby reducing the temperature, so the γ-Al2O3 undergoes a high-temperature transformation to form less α-Al2O3.

[0089] (2) Characterization of film cross-sectional morphology

[0090] Figure 4The cross-sectional morphology of the micro-arc oxidation film prepared on 2A12 aluminum alloy in the electrolyte with different concentrations of sodium oxalate, including (a) 0.0g / L; (b) 0.5g / L; (c) 1.0g / L; (d) 1.5g / L; (e) 2.0g / L. The results show that the cross-sectional morphology of the micro-arc oxidation film presents a classic three-layer structure, namely the external loose porous layer, the internal dense layer and the interface barrier layer. The external loose porous layer occupies about 1 / 5 of the thickness of the entire film, the internal dense layer is about 4 / 5 of the thickness, and the interface barrier layer is about 12m. When exposed to a corrosive environment, the external loose layer can only temporarily delay the penetration, while the internal dense layer plays a key protective role, effectively resisting the corrosion from spreading to the inside. Although the interface barrier layer is thin, it is the last line of defense for the corrosive medium to reach the substrate. Therefore, the density of the internal dense layer and the interface barrier layer is crucial to the protective performance of the film. Adding 0.5g / L sodium oxalate significantly reduces the defects of pores and cracks in the film layer compared to the unadded film layer, and the pore size is reduced, and some through cracks are blocked by oxides, which shows that adding Na2C2O4 can achieve film densification. However, when the Na2C2O4 content increases again, the defects in the film layer increase instead, and the proportion of loose porous layer in the entire film layer increases. When the Na2C2O4 concentration is added to 2.0g / L, the film layer is already occupied by the loose porous layer. From the perspective of the overall film layer, it is observed that the compactness of 0.5g / L is slightly better than 1.0g / L, followed by 1.5g / L, and the worst is without adding sodium oxalate. When the sodium oxalate concentration reaches 2.0g / L, although the film layer is very uniform, there are particularly many pores and cracks in the film layer, and ablation occurs, and the film layer is separated from the substrate. Therefore, the sodium oxalate concentration of the present invention is limited to 1.5g / L at most.

[0091] (3) Characterization of element distribution in film cross section

[0092] Figure 5The elemental surface scanning diagram of the cross section of the micro-arc oxidation film layer under different sodium oxalate concentrations, including (a) 0.0g / L; (b) 0.5g / L; (c) 1.0g / L; (d) 1.5g / L; (e) 2.0g / L. The EDS results of the cross section of the five MAO film layers show that the five film layers are mainly composed of Al, O, and Si elements. It can be seen from the figure that the Al element in the film is mainly distributed in the dense layer of the film, and the content of the external loose layer is reduced, indicating that the Al element diffuses from the aluminum matrix to the micro-arc oxidation film during the micro-arc oxidation process; the O element is mainly distributed in the entire film in the form of oxides and is relatively uniform; and the Si element is mainly distributed in the external loose layer of the film, indicating that sodium silicate in the electrolyte participates in the reaction, and the corresponding Si element diffuses from the electrolyte to the matrix. No crystal diffraction peak of Si-containing substances is found in the XRD spectrum analysis, so it is inferred that it mainly exists in the film in the form of amorphous silicon oxide. It is worth noting that when the sodium oxalate content is 2.0g / L, the Si element tends to be distributed in the entire film; the Cu element in the matrix is ​​enriched in the second phase, and the others are distributed in the matrix in the form of solid solution. Whether the film contains it needs further detection and analysis.

[0093] (4) Characterization of corrosion resistance of film layer

[0094] Potentiodynamic polarization curve test

[0095] Figure 6 The following are the potentiodynamic polarization curves of the films prepared at different sodium oxalate concentrations in a 3.5wt.% NaCl solution. Theoretically, the higher the self-corrosion potential, the lower the self-corrosion current density, and the better the corrosion resistance of the sample. Compared with the self-corrosion potential, the self-corrosion current density has a greater impact and is an important criterion for material selection. The corresponding self-corrosion potential (E corr ), self-corrosion current density (i corr ) are listed in Table 5. It can be seen from the table that the order of the self-corrosion potential is as follows: 0.5g / L>1g / L≈1.5g / L>0.g / L. When the self-corrosion potential is above about -0.3V, the film layer prepared in 0.5g / L sodium oxalate is always in a "quasi-passivation" state, that is, the electrode potential increases but the self-corrosion current density increases very slowly. When the electrode potential rises to 1.5V, the current density is still at 10 -4 Acm -2 The current density of the membrane prepared in 1.0g / L and 1.5g / L sodium oxalate increases with the increase of electrode potential. When the electrode potential rises to 1.5V, the current density reaches 10 -3 Acm -2 The current density of the membrane prepared in 0g / L sodium oxalate reached 10 at a potential above -0.3V. - 3Acm -2 The above indicates that the film layer loses its protective ability very quickly with a slight fluctuation in the electrode potential. According to the above analysis, the protective performance of the film layers prepared in different sodium oxalate electrolytes to the substrate in the corrosive medium of 3.5wt.% NaCl solution is in the order of 0.5g / L>1g / L>1.5g / L>0g / L.

[0096] Table 5 Electrical parameters corresponding to the potentiodynamic polarization curves of four MAO films

[0097] Samples <![CDATA[E corr (V)]]> <![CDATA[i corr (A·cm -2 )]]> 0.0g / L -0.716±0.005 <![CDATA[(3.99±0.532)×10 -5 ]]> 0.5g / L -0.521±0.003 <![CDATA[(3.78±0.216)×10 -8 ]]> 1.0g / L -0.635±0.002 <![CDATA[(6.71±0.324)×10 -7 ]]> 1.5g / L -0.616±0.004 <![CDATA[(2.49±0.457)×10 -6 ]]>

[0098] Electrochemical Impedance Spectroscopy (EIS) Test

[0099] The long-term corrosion resistance of four MAO films was analyzed by electrochemical impedance spectroscopy (EIS). The results are as follows: (a) 1 day, (b) 7 days, and (c) 14 days. Figure 7 As shown. The four MAO film layers all have a "three-layer" structure of a loose outer layer, a middle dense layer and a barrier layer. However, the loose outer layer has many pores and cracks. In the impedance test, the corrosive medium can easily pass through the outer loose layer to the dense layer. Therefore, the outer loose layer and the middle dense layer can be classified as loose porous parts, and these two layers are difficult to distinguish in the spectrum, so usually a time constant is shown. According to the microstructural characteristics of the film layer and the shape of the spectrum, all samples show three time constants, corresponding to the high frequency band, the medium frequency band, and the low frequency band. The capacitive reactance arc in the high frequency region represents the response of the loose porous part, the capacitive reactance arc in the medium frequency region corresponds to the response of the internal dense layer, and the capacitive reactance arc in the low frequency region represents the response of the corrosion reaction at the solution / matrix interface. Therefore, in the given fitting circuit, the capacitance and resistance (Q p and R p ) corresponds to the time constant of high frequency. The capacitance and resistance of the barrier layer (Qd and Rd) correspond to the time constant of medium frequency. Because of the occurrence of electrochemical corrosion reaction, the double layer capacitance and charge transfer resistance (Q dl and R ct ) corresponds to the appearance of low-frequency capacitive reactance arc, and the corresponding fitting circuit is as follows Figure 8As shown in Figure 8(a), all membrane layers show three time constants in the entire frequency band, and the phase angle values ​​are all less than 90°. In addition, Waburg impedance appears in the low frequency band, so the fitting circuit uses 8(a). As the immersion time increases, the high-frequency phase angle values ​​of the membrane layers obtained by 0g / L, 1g / L and 1.5g / L sodium oxalate are significantly reduced, indicating that the barrier performance of the loose porous membrane layer is sharply weakened. The corrosive medium also changes from slowly entering the internal dense layer from defects such as pores and cracks to quickly reaching the dense layer, that is, from local penetration to uniform penetration. The circuit is changed from the original series connection to the parallel connection form, and the corresponding fitting circuit is 8(b). From 7 to 14 days, the high-frequency phase angle value of the 0.5g / L membrane layer decreases, but the overall curve does not change significantly. Therefore, the circuit diagram 8(a) is always used. The high-frequency phase angle is gradually decreasing, indicating that the protective ability of the outer layer is constantly decreasing. From the mid-frequency region to the low-frequency region, the platform is wider than other membrane layers, indicating that the protective ability of the dense layer is higher than that of other membrane layers. The phase angle value of the high-frequency band of the spectrum of the film layer obtained with 1.0g / L sodium oxalate for 7-14 days decreases, and the platform of the phase angle in the medium-frequency band becomes narrower, which indicates that the overall barrier performance of the film layer gradually decreases. Since there is no obvious change in the shape of the spectrum, the corresponding fitting circuit still uses 8(b). However, the phase angle value of the high-frequency band of the film layer obtained with 0g / L and 1.5g / L sodium oxalate is close to 0 at 14 days. The effect of the entire outer layer disappears, and the merging phenomenon of the time constants in the medium-frequency region and the low-frequency region is more obvious. This indicates that a large diffusion channel for the corrosive medium has been formed in the two film layers at this time. However, due to the accumulation of corrosion products that block the large diffusion channel in the MAO film layer, the corrosive medium can only reach the substrate by slow diffusion. Therefore, the diffusion phenomenon is still observed in the impedance spectrum. From the medium-frequency region to the low-frequency region, compared with 0.5g / L and 1g / L, the platform is obviously narrowed, and the speed at which the corrosive medium reaches the substrate is very fast, indicating that the protective performance of the entire film layer gradually decreases. The corresponding fitting circuit is as follows: Figure 8 (c) The change of impedance modulus shows that the modulus of the membrane layer obtained by 0.5g / L sodium oxalate increased from 10 to -6 Reduced to 10 -5 In contrast, the modulus of the film obtained with 1.0 g / L sodium oxalate decreased by about 0.5 orders of magnitude, and the final modulus was about 7×10 -4 cm 2 , while the impedance modulus of the film obtained with 0g / L and 1.5g / L sodium oxalate was reduced to 1×10 -4 cm 2 Therefore, in terms of long-term protection performance, the protection performance of the four MAO film layers is ranked as follows: 0.5g / L>1g / L>1.5 / L≈0g / L.

[0100] Neutral salt spray test

[0101] Salt spray is a common atmospheric corrosion that exists in the natural environment and is relatively destructive. Salt spray contains a large amount of Cl - , Cl - The ion radius is small, and it can easily pass through the holes of the protective layer on the metal surface to reach the substrate, react chemically and electrochemically with the metal, and cause metal corrosion. The neutral salt spray test is a common method for testing the long-term corrosion resistance of samples after surface treatment in actual industrial production.

[0102] Fig. 9 The following is the macroscopic corrosion morphology of the micro-arc oxidation film prepared at different sodium oxalate concentrations under neutral salt spray conditions. It can be seen that 0g / L and 1.5g / L sodium oxalate have obvious corrosion spots on the surface after 7 days. As time goes by, the number of corrosion spots increases and the area is getting larger. This shows that the film has gradually lost its protective ability at this time, and a large number of corroded through holes appear inside the film, resulting in Cl - It gradually penetrates into the interface of the film layer / substrate and causes corrosion, and the corrosion products gradually reach the surface of the film layer along the corrosion channel. However, 1.0g / L sodium oxalate was observed to have very little white salt stains during the 45-day salt spray period, and no obvious corrosion points were observed, indicating that it has a good protective effect on the aluminum alloy substrate. However, 0.5g / L sodium oxalate did not undergo obvious changes on the surface during the 45-day salt spray period, and no signs of corrosion appeared, showing the best protection ability.

[0103] The results of the neutral salt spray test show that 0.5g / L exhibits the best protection performance, and the long-term protection performance of the four film layers is ranked as follows: 0.5g / L>1.0g / L>1.5g / L>0g / L. The results of the potentiodynamic polarization curve test, EIS and neutral salt spray test are consistent.

[0104] (5) The influence mechanism of Na2C2O4 on plasma spark discharge and film growth behavior

[0105] Effect of Na2C2O4 on the Spark Discharge State of Plasma

[0106] The evolution of plasma spark discharge state during the whole micro-arc oxidation process of 2A12 aluminum-copper alloy in electrolytes with different Na2C2O4 concentrations is shown in Figure 2. Fig.10 As shown, combined with the plasma spark discharge characteristics of the whole process, the micro-arc oxidation process is divided into five stages.

[0107] Stage I: The initial stage of the micro-arc oxidation process is called the anodic oxidation stage. The pulse mode at this stage is a single positive pulse, and an insulating film is generated on the surface of the sample due to violent chemical and electrochemical reactions. A large number of bubbles appear on the surface of all samples and the metallic luster is lost. However, the voltage at this stage does not reach the breakdown voltage of the insulating film layer, so no plasma spark discharge phenomenon is observed on the surface of the sample.

[0108] Stage II: This stage still uses the single forward pulse mode. In this stage, the applied voltage value exceeds the breakdown voltage of the insulating film, and plasma spark discharge occurs on the sample surface. In the 0g / L sodium oxalate solution, obvious discharge occurs at the edge of the sample, but no obvious discharge occurs in the center of the sample. In comparison, other samples have obvious discharge on the entire surface, and the amount of gas precipitated is also large.

[0109] Stage III: When the forward voltage value increases to 450V, compared with the previous stage, the plasma spark discharge on the sample surface is more intense, the number of discharge points is relatively reduced, and the size is increased. The sample in 0g / L sodium oxalate solution shows bright white sparks, while the spark discharge state of the sample with sodium oxalate added gradually becomes more intense as the sodium oxalate concentration increases, and the color also changes from white-orange-yellow-orange-red. This shows that sodium oxalate enhances plasma spark discharge.

[0110] Stage IV: A negative pulse is applied in this stage. The figure shows the coexistence of "arc" discharge and "soft" spark discharge, from the initial very intense state to the state where the discharge point size and intensity gradually decrease.

[0111] Stage V: This stage is a stable stage. Plasma spark discharge always occurs at the weak position of the film layer. When the "arc" discharge and "soft" spark discharge in stage IV continue to weaken, it means that the film layer gradually thickens, and the weak points are "repaired" little by little with the occurrence of plasma spark discharge, until the thickness and density of the entire film layer reach a similar state, and only weak "soft spark" discharge remains on the surface of the sample.

[0112] The process between stage IV and stage V is called "conversion". It can be seen from the figure that the addition of sodium oxalate promotes the entire "conversion", and the higher the sodium oxalate content, the faster the "conversion" process, which means that the time taken for the film layer to reach a certain uniformity and thickness is shorter.

[0113] Effect of Na2C2O4 on film thickness / hardness

[0114] Fig.11These are the experimental results of the thickness of the film layer under different sodium oxalate concentrations. Under the condition of ensuring the same negative pulse time, it can be seen that the thickness of 0.0g / L and 0.5g / L sodium oxalate is about 50μm. When sodium oxalate is added to 1g / L, the thickness reaches 60μm, and the thickness is significantly improved. However, when sodium oxalate is added to 1.5g / L, the thickness drops to 53μm. According to the information on plasma spark discharge, sodium oxalate promotes plasma spark discharge and accelerates the "conversion" process of the film layer. Combined with the film thickness results, it can be seen that sodium oxalate increases the growth rate of the film layer. However, when the sodium oxalate concentration increases to 1.5g / L, the thickness decreases instead. The reasons for this result will be further discussed later.

[0115] Fig.12 It is the hardness value of the micro-arc oxidation film prepared by adding different sodium oxalate concentrations. According to the hardness calculation results of taking the average value after 5 measurements, it can be seen intuitively from the figure that in the loading process under the same test conditions, with the increase of sodium oxalate concentration, the hardness value shows a trend of first increasing and then gradually decreasing, and the hardness value of the micro-arc oxidation film at 0.5g / L sodium oxalate reaches a peak value, with an average value of 1301.9HV, far exceeding other sodium oxalate concentrations. The main reason is that the oxide film contains more α-Al2O3, which enhances the microhardness value of the film. The second is 1.0g / L sodium oxalate, with an average hardness of 1180.4HV. With the increase of film thickness, the density of the film also increases, which enhances the microhardness value. The hardness values ​​of 1.5g / L and 0g / L sodium oxalate are the worst, which are 1080.7HV and 1066.9HV respectively. This is consistent with the morphology of the microstructure. There are many defects inside the film layer. The less the content of α-Al2O3 phase, the lower the hardness value of the film layer. Although it is known that the plasma spark discharge will promote the formation of α-Al2O3 due to the violent discharge and high temperature. However, it is not the case that the higher the sodium oxalate content, the greater the hardness value of the film layer. It can be seen that the hardness of the film layer is proportional to these two factors: ① α-Al2O3 content; ② film density.

[0116] 3. The influence mechanism of different Na2C2O4 concentrations on film-forming behavior

[0117] The cross-sectional element distribution results have been discussed. In order to determine whether the film layer contains Cu element, the present invention further uses line scanning to determine it. Fig.13This is an analysis of the changing trend of the Cu and Si element intensity of the micro-arc oxidation film cross-section under different sodium oxalate concentrations. The line scan direction is from the substrate to the film surface. As can be seen from the figure, there is Cu element in the film. Combined with the previous surface scanning results, it can be seen that the Al and Cu in the 2A12 aluminum-copper alloy substrate and the Si in the electrolyte participate in the reaction through the plasma electrolysis process, and finally form oxides in the film. Through longitudinal comparison, it is found that the Cu element shows a downward trend from the substrate to the outer surface of the film, while the Si element shows an upward trend from the substrate to the outer surface of the film. Through lateral comparison, it is found that when the sodium oxalate concentration is from 0g / L to 2g / L, the amount of Cu element in the film increases with the increase of Na2C2O4, and the amount of Si element in the film also increases with the increase of Na2C2O4 concentration, especially when the concentration of Na2C2O4 is higher than 1.5g / L. It is very obvious. Combined with the plasma spark discharge state, the addition of Na2C2O4 will promote plasma spark discharge and promote the components in the solution to participate in the reaction, so the Si element content increases. The increase in Cu content is due to C2O4 2- It has a complexing effect, releasing Cu from the matrix 2+ 、Al 3+ The metal ions are "stabilized" and when a negative pulse is applied, they will return to the interface between the substrate and the solution to participate in the reaction, which improves the efficiency of the ion reaction. The change in the Cu element content in the film itself is because the film layer close to the substrate is denser. Compared with the outer layer, under high temperature conditions, Cu oxide decomposes into Cu 2+ Migration into solution is more difficult.

[0118] Based on the above analysis, it is found that the effects of Na2C2O4 are as follows: ① Induce plasma spark discharge; ② Promote the "conversion" process and increase the film growth rate; ③ C2O4 2- It has complexing effect and improves the utilization rate of metal ions; ④ From the previous literature research, it is known that C2O4 2- The gas contact angle is reduced and the gas escape is promoted. In combination with the above points, the present invention proposes the influence mechanism of Na2C2O4 on film formation in the micro-arc oxidation process, such as Fig.14 shown.

[0119] Under the condition of a single positive pulse, the greater the concentration of sodium oxalate added, the more intense the plasma spark discharge. Alloy elements such as Al, Cu, and Mg in the matrix enter the solution in the form of cations through oxidation reactions (Cu is used as an example here to illustrate the process of alloy elements entering the film layer). When a bidirectional pulse is applied, the film growth behavior in the electrolyte with sodium oxalate added has changed significantly, the plasma spark discharge "conversion" process is accelerated, and the film growth rate increases. Fig.14As shown in (a), the entire film layer is initially a simple outer layer and an inner layer. According to the research results of Cheng et al., plasma spark discharges are divided into several types: Type A discharge is a gas discharge, which promotes the solution components to participate in the oxidation reaction; Type B discharge has a very high intensity, strongly dissolves the matrix and releases a large amount of gas; Type C and D discharges reduce the defects of the barrier layer and the internal dense layer, and allow the Si element in the solution to be doped into the film layer; Type E discharge causes the external loose layer to melt and condense and finally densify.

[0120] When a small amount of sodium oxalate is added, C2O4 2- Will react with metal cation Al 3+ , Cu 2+ A relatively stable complex is formed, and a part of the metal cations directly participate in the film-forming reaction. When the reverse pulse is applied, the complexed metal cations in the solution will migrate to the vicinity of the substrate and re-participate in the film-forming reaction, thus improving the ion utilization rate. 2- Promotes different types of plasma spark discharges, some C2O4 2- Due to the high temperature, it will decompose to generate CO and CO2, which further promotes the gas discharge on the surface. Therefore, the components in the solution participate in the film formation, and the Si elements gathered on the surface increase. The matrix discharge is very intense, and after the oxide is formed, a series of processes such as melting-condensation-film formation also occur. 2- It can accelerate the gas escape. When the molten oxide meets the electrolyte before condensation, most of the O2, H2, CO and CO2 generated quickly escape. The molten-condensed oxide closes the discharge channel just at the location, and the defects such as pores and cracks are less. In addition, plasma spark discharge also occurs at the interface between the inner layer / outer layer and the electrolyte, further reducing the defects between the film layers. The film layer formed after the discharge is as follows: Fig.14 (b). The subsequent plasma spark discharge will transfer to the next weak point, and the cycle will repeat, showing a "repairing" effect in the film layer, and finally achieving film densification.

[0121] C2O4 2- The role of the micro-arc oxidation process can be summarized into two aspects: first, it complexes metal cations, increases ion utilization, promotes plasma spark discharge, and accelerates film growth; second, it increases the gas escape rate and reduces defects in the film. The two aspects work synergistically. Compared with the film without sodium oxalate, as the concentration of sodium oxalate increases, the content of Si and Cu elements in the film increases, the film thickness increases, the defects are significantly reduced, the high-temperature stable phase α-Al2O3 in the film increases, and the hardness is improved.

[0122] When the added sodium oxalate content increases further, Fig.14 (c) As shown, C2O4 2-It will complex more metal cations and increase the metal ion reaction efficiency. The line scan results show that the Cu content in the film layer has indeed increased. 2- The decomposition of CO and CO2 also increased significantly. In addition, the increase in sodium oxalate concentration promoted plasma spark discharge, and the generation of O2 and H2 also increased. When the oxide undergoes the process of melting-condensation-film formation, due to the large amount of gas, the oxide has encountered the electrolyte condensation, and the gas has not been released completely, resulting in a lot of gas being trapped in the oxide film layer at the moment of film formation. Later, the gas is slowly released from the film layer again, which will further leave a gas release channel, resulting in an increase in defects and cracks in the film layer, reducing the protective performance of the film layer. The results are as follows: Fig.14 (d) As shown. The increase in sodium oxalate content promotes plasma spark discharge, increases the electrolyte composition and metal cation utilization rate, so the line scan results show that the sodium oxalate content increases, and the Si and Cu element contents in the film layer increase. However, when the sodium oxalate content increases, a part of the molten oxide in the film layer will be dispersed and splashed into the electrolyte due to a large amount of gas release, and there is no time to condense to form an oxide film layer. Therefore, the thickness of the film layer does not increase with the increase of sodium oxalate. When the content is too high (such as 2g / L in the present invention), the bonding force of the film layer deteriorates, and even ablation occurs. Due to the presence of too many defects in the corresponding film layer, it is impossible to achieve a good heat preservation effect during the plasma spark discharge process, so the high-temperature stable phase finally formed is reduced and the hardness decreases. That is to say, when the sodium oxalate content is too high, although it promotes plasma spark discharge and accelerates the "conversion" process, due to the dominant position of gas release, the synergistic effect of the two aspects is "unbalanced" at this time, resulting in failure of film densification.

[0123] In summary, the addition of sodium oxalate can indeed achieve film densification, which is due to the synergistic effect of the two aspects discussed above. The most suitable range of sodium oxalate in the present invention is 0.5-1.0 g / L.

[0124] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0125] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an aluminum-copper alloy micro-arc oxidation film, characterized in that: The following steps are involved: Pre-treating the base material; preparing a micro-arc oxidation electrolyte, wherein the electrolyte in the micro-arc oxidation electrolyte consists of sodium silicate, sodium hydroxide and soluble oxalate, and the solvent is water; In the micro-arc oxidation electrolyte, the concentration of sodium silicate is 2.5 g / L to 7.5 g / L, the concentration of sodium hydroxide is 2 g / L to 5 g / L, and the concentration of soluble oxalate is 0.5 g / L to 1.5 g / L; The pretreated substrate material is placed in a micro-arc oxidation electrolyte for micro-arc oxidation to obtain an aluminum-copper alloy micro-arc oxidation film layer, wherein the specific electrical parameters of the micro-arc oxidation are: current density 3A / dm 2 ~5A / dm 2 , the pulse frequency is 300Hz~600Hz, and the duty cycle is 12%~18%.

2. The method for preparing an aluminum-copper alloy micro-arc oxidation film according to claim 1, characterized in that: The soluble oxalate is sodium oxalate, potassium oxalate or ammonium oxalate.

3. The method for preparing an aluminum-copper alloy micro-arc oxidation film according to claim 1, characterized in that: The concentration of soluble oxalate in the micro-arc oxidation electrolyte is 0.5 g / L.

4. The method for preparing an aluminum-copper alloy micro-arc oxidation film according to claim 1, characterized in that: The specific electrical parameters of micro-arc oxidation are: current density is 3A / dm 2 , the pulse frequency is 600Hz and the duty cycle is 12%.

5. The method for preparing an aluminum-copper alloy micro-arc oxidation film according to claim 1, characterized in that: The micro-arc oxidation treatment time is 2h~3h, and the treatment temperature is 30℃~40℃.

6. The method for preparing an aluminum-copper alloy micro-arc oxidation film according to claim 1, characterized in that: The base material is aluminum-copper alloy.

7. An aluminum-copper alloy micro-arc oxidation film layer obtained by the preparation method according to any one of claims 1 to 6.

8. The copper-aluminum alloy micro-arc oxidation film layer according to claim 7, characterized in that: The micro-arc oxidation film has a thickness of 50 μm to 60 μm and a hardness of 1180.42 HV to 1301.94 HV.

Citation Information

Cited By

  • Micro-arc oxidation film layer with sandwich structure and preparation method of micro-arc oxidation film layer

    CN122327331A